Running Wild - Johnson, Margaret (United Kingdom Cambridge University Press, 2009)
Luke and Alex are neighbors and, on Luke's part, reluctant friends. They spend their free time on a large heath, looking for anything to keep themselves amused. Meanwhile an illegally-kept panther escapes its owner and takes refuge on the same heath. The paths of the boys and the cat are destined to meet.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Reading books; Language Learning; Fiction; Adventure; Lower-intermediate Level